98 Comparison of digestibility of forages in Jersey steers supplemented with a yeast fermentation product on a high and low quality forage diet. (29th July 2019) - Garcia, Anissa R; Boyd, Jamie; Splan, Rebecca
Abstract: The objective of this study was to determine the effect on digestibility of forages using a daisy jar system with inoculum from steers supplemented with the yeast fermentation product Saccharomyces cerevisiae . Forages tested included ryegrass, wheat, orchard grass, alfalfa, and sorghum sudan hays. Samples were ground through a 1mm screen, placed in Ankom F57 bags, and run in triplicate to increase statistical significance. Two ruminally cannulated jersey steers were used in a switchback design. Animals were housed in a dry lot pen. The study consisted of 2 three-week periods, 2-week standardization followed by a 1-week test period. Diets offered for period 1 were steer A = 100% alfalfa hay w/o yeast product and steer B = 100% wheat hay w/o yeast product. Diets offered for period 2 were steer A =100% alfalfa hay +15g/h/d yeast product and steer B =100% wheat hay +15g/h/d yeast product. During the test week, rumen fluid contents were collected from each donor via rumen cannula approximately 4 h after feeding and taken to the lab to be composited. The samples were incubated for 0 h, 24 h, 48 h, 72 h, and 96 h. At the end of the incubation period bags were collected and cold shocked to stop microbial digestion. Samples were dried at 55 o C and stored for later analysis. Model included trt (+/-yeast), forage, hr, and interactions forage*hr and forage*trt. No significant differences were observed (P = 0.38) on DM digestibility or NDF digestibility (P = 0.76) with the supplementation of yeast fermentation product. Forage*Trt was significant (P = 0.03 DMdig, P = 0.02 NDFdig). Implications of this study are the inclusion of a Saccharomyces cerevisiae fermentation product at a rate of 15g/h/d may not impact overall forage NDF or DM digestibility but may impact types of forage differently in an in vitro system using composited inoculum from donors on a forage diet.